Cardiovascular and hepatic disease associations by magnetic resonance imaging: A retrospective cohort study - Kwan, Alan C.; Sun, Nancy; Driver, Matthew; Botting, Patrick; Navarrette, Jesse; Ouyang, David; Hussain, Shehnaz K.; Noureddin, Mazen; Li, Debiao; Ebinger, Joseph E.; Berman, Daniel S.; Cheng, Susan (Frontiers in Cardiovascular Medicine, 2022)
Background. Hepatic disease is linked to cardiovascular events but the independent association between hepatic and cardiovascular disease remains unclear, given shared risk factors. Methods. This was a retrospective study of consecutive patients with a clinical cardiac MRI (CMR) and a serological marker of hepatic fibrosis, the FIB-4 score, within one year of clinical imaging. We assessed the relations between FIB-4 scores grouped based on prior literature: low (<1.3), moderate (1.3-3.25), and high (>3.25), and abnormalities detected by comprehensive CMR grouped into 4 domains: cardiac structure (end diastolic volumes, atrial dimensions, wall thickness); cardiac function (ejection fractions, wall motion abnormalities, cardiac output); vascular structure (ascending aortic and pulmonary arterial sizes); and cardiac composition (late gadolinium enhancement, T1 and T2 times). We used Poisson regression to examine the association between the conventionally defined FIB-4 category (low <1.3, moderate 1.3-3.25, and high >3.25) and any CMR abnormality while adjusting for demographics and traditional cardiovascular risk factors. Results: Of the 1668 patients studied (mean age: 55.97±17.28, 901 [54%] male), 85.9% had ≥1 cardiac abnormality with increasing prevalence rates seen within the low (82.0%) to moderate (88.8%) to high (92.3%) FIB-4 categories. Multivariable analyses demonstrated the presence of any cardiac abnormality was significantly associated with having a high-range FIB-4 (prevalence ratio 1.07, 95% CI:1.01-1.13); notably, the presence of functional cardiac abnormalities were associated with being in the high FIB-4 range (1.41, 1.21-1.65) and any vascular abnormalities with being in the moderate FIB-4 range (1.22, 1.01-1.47). Conclusions: Elevated FIB-4 was associated with cardiac functional and vascular abnormalities even after adjustment for shared risk factors. These CMR findings indicate that cardiovascular abnormalities exist in the presence of subclinical hepatic fibrosis, irrespective of shared risk factors, underscoring the need for further studies of the heart-liver axis.